Distribution of Heavy Metals in Water, Sediment and Fishes of the Baram River of Northern Sarawak, Malaysia - Mugilan, Rajendran (Universiti Malaysia Sarawak (UNIMAS), 2017)
This study reports the heavy metals content in water, sediment and fishes of Baram River. Water samples were digested according to open acid digestion method whilst sediment and fish were digested using microwave digestion. The samples were subjected to Microwave Plasma-Atomic Emission Spectrometer for metals (AI, As, Cr, Cu, Fe, Mn, Ni, Pb, Se and Zn) analysis. Hg was analysed using mercury analyser. The metals concentration in water was compared with NSDWQ guidelines whereas for sediment, Sediment Quality Guidelines was used. In water, Al (0.34 mgIL) and Fe (0.86 mg/L) were found close to/above the guidelines at stations with settlement, land erosion and logging activities. Al (39,215 mg/kg) and Fe (21,073 mg/kg) were predominantly found in sediment due to the natural abundance. Contamination assessment suggests no concern of pollution in sediment at the moment however; some stations at downstream were characterized with increasing metals. Gills accumulated relatively average higher concentrations of Al (293 .01 mg/kg), Fe (171.10 mg/kg), Mn (77.36 mg/kg) and Zn (103 .74 mg/kg) whilst Hg (0.79 mg/kg) was consistently found in elevated concentration in muscle. Carnivorous species including Hampala bimaculala and Kryploplems apogon shows hazard index more than I. In comparison to the guideline, herbivorous Barbonymlls schwanenfeldii (2.3 1 mg/kg w/w) and Punliopliles waandersi (3 .59 mg/kg w/w) shows higher Al concentration compared to permissible level (2.0 mg/kg w/w). Futhermore, Kryploptel1ls apogon (0.34 mg/kg w/w) and Hampala bimaclllala (0.26 mg/kg w/w) found Hg concentration slightly below the permissible level 0.5 mg/kg w/w. The results of this study indicate that the water, sediment and fishes are categorized as low risk of contamination, thus no pollution and the consumption of the fish are safe except the 4 species mentioned above.